Influence of alumina on physical properties of an industrial zinc–copper smelting slag Part 3 – melting behaviour. (March 2013) - Mostaghel, S; Matsushita, T; Samuelsson, C; Björkman, B; Seetharaman, S
Abstract : A combination of different experimental techniques and thermodynamic calculations has been used to investigate the melting behaviour of an industrial iron silicate slag and mixtures of this slag with 5, 10 and 15 wt-% alumina addition. Differential scanning calorimetry (DSC) and thermo-optical observation were applied to monitor the solidus temperature and softening behaviour of the samples respectively. Estimation of the liquidus temperature was made using the second derivative of activation energies for viscous flow, with respect to temperature. All experimentally detected values were compared to predictions made using the FactSage TM 6·2 thermodynamic package. Results show that as the slag lies in the fayalite primary phase field, the liquidus temperature decreases due to the increased alumina concentration. In the hercynite primary crystallisation phase field, however, alumina addition to the system increases the liquidus temperature. The solidus temperature does not vary significantly due to the current changes in the total alumina content of the slag.